Towards a funambulist leadership in researchers well-being: Managing equilibriums and tensions in the hybrid work era - Jacinto G. Lorca; Simone Belli (Administrative Sciences, 2023)
The chaotic adaptation to hybrid work during the COVID-19 pandemic has meant that workers still do not know how professional dynamics function correctly in this new context. In this paper, we focus on new issues that have arisen in this era of hybrid work, with the aim of improving performance, conciliation, and well-being in the specific professional environments of universities and research institutes. We will show the results from a non-representative survey comprising 451 scientists. Aspects such as management and leadership over their work, the purpose to achieve something innovative in their work, and promoting well-being in their work spaces and co-workers, have been observed and identified in the survey. The figure of a leader emerges as someone who is communicative, collaborative, and that helps colleagues and their professional development. We suggest that a tightrope walker leader, that is, one who knows how to strike a balance between individual needs and collective interests, could be the key to ensuring the well-being of scientists.
Keywords: 350; leadership; hybrid work; scientific collaboration; virtual groups; well-being